ANALISIS INSTRUMEN PASAR MODAL SYARIAH DALAM PERSPEKTIF HUKUM ISLAM - , Lanugranto Adi Nugroho, SH; , Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research means to know (1) the comparison and the differentiation between the sharia capital market instrument and the conventional capital market instrument.(2) to know the considering of positive law about sharia capital market instrument. (3) to know the sharia Islamic law paradigm about sharia capital market instrument in Indonesia. This research includes on the normative research with the explanative descriptive as its character. It uses the secondary data such as the positive law with another literature. The data analysis is the interactive data analysis that consists of the data collection, the data preview, the data reduction, and the conclusion. As its conclusions,(1) there are differentiations between the sharia capital market instrument and the conventional capital market instrument namely the screening process, the adoption of the profit and loss sharing system with no special right and its differential in sharia capital market instrument.(2) no specific/positive law that give legitimation to sharia capital market instrument and (3) according to the agreement of fuqaha, it allows the trading of sharia capital market instrument such as stock, obligation, and mutual fund.